Successful Pregnancy Outcome in Women with Recurrent IVF Failure and Anti-hCG Autoimmunity: A Report of Three Cases - Valeria Muller; Ksenia Ob’edkova; Inna Krikheli; Igor Kogan; Irina Fedorova; Elena Lesik; Evgenia Komarova; Alexandr Gzgzyan (Case Reports in Immunology)
We report three cases of effective management of infertility in women with a history of repeated unsuccessful IVF attempts, who have developed antibodies to hCG. A novel approach to conservative treatment of immunologic reproductive failure, suggested for selected patients, included membrane plasmapheresis, combined prednisolone, and intravenous immunoglobulin therapy. No adverse side effects were observed; all cases resulted in pregnancy and subsequent life births. In order to be given an adequate efficient treatment, women with recurrent implantation failure should be suspected for autoimmune factor of infertility and its possible association with anti-hCG autoimmunity.